2018
DOI: 10.1177/1708538118772682
|View full text |Cite
|
Sign up to set email alerts
|

Common femoral artery endarterectomy in the age of endovascular therapy

Abstract: CFE is a reliable and dependable procedure, even in the absence of good distal runoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…These efficacy findings align with published studies of femoral endarterectomy with patch angioplasty, which have reported 1-year and long-term patency rates of 90-100% and 85-96%, respectively (78)(79)(80)(81)(82). However, limited prospective evidence has been published comparing outcomes of SIS-ECM with different types of patches for femoral endarterectomy.…”
Section: Sis-ecm In Iliofemoral Artery Reconstruction-perform Studysupporting
confidence: 85%
“…These efficacy findings align with published studies of femoral endarterectomy with patch angioplasty, which have reported 1-year and long-term patency rates of 90-100% and 85-96%, respectively (78)(79)(80)(81)(82). However, limited prospective evidence has been published comparing outcomes of SIS-ECM with different types of patches for femoral endarterectomy.…”
Section: Sis-ecm In Iliofemoral Artery Reconstruction-perform Studysupporting
confidence: 85%
“…Management of CFA lesions is challenging. Surgical treatment and endarterectomy of CFA lesions has been proved to be safe and reliable procedure [1][2][3][4]. Elsherif et al [4] has reported the outcome of 1134 revascularization procedures due to critical limb ischemia, out of which 66 CFA endarterectomies with favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment and endarterectomy of CFA lesions has been proved to be safe and reliable procedure [1][2][3][4]. Elsherif et al [4] has reported the outcome of 1134 revascularization procedures due to critical limb ischemia, out of which 66 CFA endarterectomies with favorable outcome. However, improvement in endovascular procedures in recent years, has resulted in numerous publications showing good results of endovascular treatment of CFA lesions [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common femoral artery endarterectomy (CFAe) is a well-established therapy to treat peripheral artery disease. Previous studies have demonstrated good shortterm and mid-term patency rates (1)(2)(3)(4)(5)(6)(7)(8). However, long-term results have been infrequently published.…”
Section: Introductionmentioning
confidence: 99%